Influence of epidemiology, immunosuppressive regimens, clinical presentation, and treatment on kidney transplant outcomes of patients diagnosed with tuberculosis: A retrospective cohort analysis. Issue 5 (17th January 2019) - Viana, Laila Almeida; Cristelli, Marina P.; Santos, Daniel Wagner; Tavares, Melissa G.; Dantas, Marcus Taver C.; Felipe, Claudia Rosso; Silva, Helio Tedesco; Pestana, Jose Medina
Abstract : Tuberculosis (TB) mortality is high among kidney transplant (KT) recipients. Although local epidemiology is an important factor, diagnostic/therapeutic challenges and immunosuppressive therapy (ISS) may influence outcomes. We analyzed the cumulative incidence (CumI) of TB in KT recipients receiving a variety of ISS with long‐term follow‐up. Our retrospective single‐center cohort study included all KT procedures performed between January 1, 1998, and August 31, 2014, with follow‐up until August 31, 2014. Induction therapy was based on perceived immunological risk; maintenance ISS included prednisone and calcineurin inhibitor (CNI) plus azathioprine (AZA), and mycophenolic acid (MPA) or mechanistic target of rapamycin inhibitor (mTORi). Thirty‐four patients received belatacept/MPA. KT was performed on 11 453 patients and followed for 1989 (IQR 932 to 3632) days. Among these, 152 patients were diagnosed with TB (CumI 1.32%). Median time from KT to TB was 18.8 (IQR 7.2 to 60) months, with 59% of patients diagnosed after the first year. Unadjusted analysis revealed an increasing confidence interval (CI) of TB (0.94% CNI/AZA vs 1.6% CNI/MPA [HR = 1.62, 95% CI = 1.13 to 2.34, P = .009] vs 2.85% CNI/mTORi [HR = 2.45, 95% CI = 1.49 to 4.32, P < .001] vs 14.7% belatacept/MPA [HR = 13.14, 95% CI = 5.27 to 32.79, P < .001]). Thirty‐seven (24%) patients died, and 39 (25.6%) patients experienced graft loss. Cytomegalovirus infection ( P = .02) and definitive ISS discontinuation ( P < .001) were associated with death. Rejection ( P = .018) and ISS discontinuation ( P = .005) occurred with graft loss. TB occurred at any time after KT and was influenced by ISS. Abstract : This large case series from an endemic area underscores the burden of tuberculosis after kidney transplantation, including the influence of immunosuppressive regimens, challenging diagnosis and treatment, and poor outcomes. Fishman's accompanying editorial is onpage 1262 .